Rethinking leadership behaviour in Higher Education in Malaysia. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2008)
The last two decades have seen the world of higher education undergoing tremendously difficult times.Academic capitalism, managerialism and economic rationalism (Mok, 2007), driven by the growth of neo-liberalism and the dominance of knowledge-based economy are challenging the fundamental ethos of the academe. In such uncertain times, leadership is critical to chart the development of higher education institutions (HEIs). In some countries, the decline in institutional resources (Johnstone, 1999), changing student demographics (Hutardo and Dey, 1997), shift towards student-centered learning (Barr and Tagg, 1995), impact of technology on faculty role (Baldwin, 1998), and more recently the shift from industrial age to a knowledge age (Dolence and Norris, 1995) have made leadership a key success factor in transforming HEIs. These issues are compounded by the growing trend of cross-border and transnational higher education (Knight, 2006; Huang, 2007; Morshidi, 2006).